Curriculum and Instructional Quality - Nita, Khairo; Sesmiarni, Zulfani (Early Publishing, 2026)
The quality of curriculum and learning has become a critical issue in improving educational outcomes, particularly in the context of Islamic education, which emphasizes both intellectual and moral development. However, many educational institutions still face challenges such as irrelevant curricula, teacher-centered learning practices, limited integration of technology, and ineffective evaluation systems. This study aims to analyze the concept of curriculum quality, examine the development of quality-based learning, explore the role of Higher Order Thinking Skills (HOTS) and digital learning, and evaluate learning practices based on quality principles. This research employs a qualitative approach using a library research method, analyzing relevant literature from scientific journals and academic sources published within the last ten years. The findings indicate that curriculum quality must be integrative, flexible, and aligned with contemporary needs while maintaining Islamic values. In addition, effective learning requires student-centered approaches supported by teacher competence, innovation, and technology integration. The study also reveals that HOTS and digital learning significantly enhance critical thinking and learning engagement, while continuous and comprehensive evaluation is essential to ensure learning effectiveness. In conclusion, improving educational quality requires a holistic and integrated approach involving curriculum reform, innovative learning strategies, and sustainable evaluation systems.